Immunosuppression and malignant neoplasms: Risk-benefit assessment in patients with inflammatory bowel disease - Moutinho, Bruna Damásio [UNESP] (2020)
Objective: Adverse events of drug therapy Background: The treatment of inflammatory bowel disease aims to induce and maintain disease remission, avoid complica-tions, and restore quality of life. The treatments include the use of immunosuppressants and biological therapy. Despite the effectiveness of these treatments in controlling disease activity and in limiting complications, there remains an increased risk of developing malignancies. Case Report: A 70-year-old male patient with ulcerative colitis who had pancolitis was initially treated with mesalazine. In 2010, the medication was changed to azathioprine due to clinical disease activity. The patient demonstrated clinical and endoscopic response to the medication, but presented recurrent facial lesions identified as non-mela-noma skin cancer in 2014, 2015, and 2016. Azathioprine was discontinued and anti-TNF therapy was started, but no satisfactory clinical or endoscopic response was observed. The patient developed hematuria and a ure-ter tumor was found with subsequent ureteronephrectomy. Moreover, the patient underwent total colectomy with ileostomy as a treatment for refractory ulcerative colitis. Conclusions: Immunosuppressive therapy can facilitate the development of malignant neoplasms, accelerate tumor growth, and favor the onset of metastases. The types of tumors most associated with its use are lymphoproliferative tumors and non-melanoma skin cancer. The benefits of adequate control of inflammatory bowel disease are clear and the use of immunosuppressants should not be limited by these potential adverse outcomes; how-ever, the risk-benefit profile of immunosuppression should always be assessed on a case-by-case basis.